2017
DOI: 10.1002/bsl.2311
|View full text |Cite
|
Sign up to set email alerts
|

Diversion at re‐entry using criminogenic CBT: Review and prototypical program development

Abstract: Society and the criminal justice system prioritize the reduction of reoffending risk as part of any criminal justice intervention. The Sequential Intercept Model identifies five points of interception at which justice-involved individuals can be diverted into a more rehabilitative alternative: (1) law enforcement/emergency services; (2) booking/initial court hearings; (3) jails/courts; (4) re-entry; and (5) community corrections/community support. The present article focuses on diversion as part of Intercept 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…A 2010 study conducted in California found that participants in FACT were significantly less likely to be rearrested than their peers in a control group in both the first and second years following release (Cusack et al, 2010). Other research has confirmed this pattern among participants of FACT programs implemented elsewhere (Heilbrun et al, 2017;Lamberti et al, 2011). Another study revealed remarkably encouraging results, with positive outcomes related to multiple domains, including ''nonreoffending, psychiatric stability, substance abuse abstinence, stable housing and meaningful activity'' (Smith et al, 2010).…”
Section: Forensic Assertive Community Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2010 study conducted in California found that participants in FACT were significantly less likely to be rearrested than their peers in a control group in both the first and second years following release (Cusack et al, 2010). Other research has confirmed this pattern among participants of FACT programs implemented elsewhere (Heilbrun et al, 2017;Lamberti et al, 2011). Another study revealed remarkably encouraging results, with positive outcomes related to multiple domains, including ''nonreoffending, psychiatric stability, substance abuse abstinence, stable housing and meaningful activity'' (Smith et al, 2010).…”
Section: Forensic Assertive Community Treatmentmentioning
confidence: 99%
“…FACT adjusts the focus of treatment to preventing future incarcerations and usually involves the patient's parole officer as a member of the multidisciplinary treatment team (Lamberti et al, 2011). The parole officer undergoes mental health training prior to engaging in the program, which has been shown to increase agreement between officers and other members of the team when making decisions regarding the patient's treatment and/or potential disciplinary action (Heilbrun et al, 2017).…”
Section: Forensic Assertive Community Treatmentmentioning
confidence: 99%
“…Regarding specific psychotherapeutic orientations, cognitive behavior therapy (CBT) has garnered a strong track record with respect to treating justice-involved persons (Antonio & Crossett, 2017; Harrison et al, 2020; Higgs et al, 2018; Mpofu et al, 2018; Olver et al, 2020; Yoon et al, 2017). The Drexel Reentry Project (DRP) developed to address the needs of moderate- to high-risk justice-involved persons at community reentry, uses CBT principles in its multistep program (Heilbrun et al, 2017). Of note, DRP (2020) moved to telehealth in the context of COVID.…”
Section: Research Priorities For Forensic E-mental Healthmentioning
confidence: 99%
“…Furthermore, interventions focused on enhancing motivation could promote service utilization and engagement, as well as overall treatment response. 77,78 No study, to the best of our knowledge, has examined responsivity-general or specific-in the context of mental health jail diversion programs. Nonetheless, responsivity may be the key to reducing public safety risk and improving outcomes among justice-involved persons with mental health problems.…”
Section: Informing Decisionsmentioning
confidence: 99%